Neuropsychological and social cognitive function in young people at genetic risk of bipolar disorder. Issue 4 (1st December 2015) - McCormack, C.; Green, M. J.; Rowland, J. E.; Roberts, G.; Frankland, A.; Hadzi-Pavlovic, D.; Joslyn, C.; Lau, P.; Wright, A.; Levy, F.; Lenroot, R. K.; Mitchell, P. B.
Abstract : Background: Impairments in key neuropsychological domains (e.g. working memory, attention) and social cognitive deficits have been implicated as intermediate (endo) phenotypes for bipolar disorder (BD), and should therefore be evident in unaffected relatives. Method: Neurocognitive and social cognitive ability was examined in 99 young people (age range 16–30 years) with a biological parent or sibling diagnosed with the disorder [thus deemed to be at risk (AR) of developing BD], compared with 78 healthy control (HC) subjects, and 52 people with a confirmed diagnosis of BD. Results: Only verbal intelligence and affective response inhibition were significantly impaired in AR relative to HC participants; the BD participants showed significant deficits in attention tasks compared with HCs. Neither AR nor BD patients showed impairments in general intellectual ability, working memory, visuospatial or language ability, relative to HC participants. Analysis of BD-I and BD-II cases separately revealed deficits in attention and immediate memory in BD-I patients (only), relative to HCs. Only the BD (but not AR) participants showed impaired emotion recognition, relative to HCs. Conclusions: Selective cognitive deficits in the capacity to inhibit negative affective information, and general verbal ability may be intermediate markers of risk for BD; however, the extent and severity of impairment in this sample was less pronounced than has been reported in previous studies of older family members and BD cases. These findings highlight distinctions in the cognitive profiles of AR and BD participants, and provide limited support for progressive cognitive decline in association with illness development in BD.